The Use of Hydroponics in the Practice of Forestry - Olson, R. V. (Indian Forester, 1944)
Growing forest seedlings in nurseries entails a great deal labor and time. The use of "hydroponics," or "soilless cultures," promises to accelerate the production of mature planting stock and to improve its quality. In this methods, the seedlings are grown from seed in nutrient solutions in early spring and after several weeks are transplanted to nursery beds for further development and hardening. This paper reports the results of an investigation of various aspects of hydroponics in forestry practice.